Closing the Nanographene Gap: Surface‐Assisted Synthesis of Peripentacene from 6, 6′‐Bipentacene Precursors. Issue 50 (20th October 2015) - Rogers, Cameron; Chen, Chen; Pedramrazi, Zahra; Omrani, Arash A.; Tsai, Hsin‐Zon; Jung, Han Sae; Lin, Song; Crommie, Michael F.; Fischer, Felix R.
Abstract: The thermally induced cyclodehydrogenation reaction of 6, 6′‐bipentacene precursors on Au(111) yields peripentacene stabilized by surface interactions with the underlying metallic substrate. STM and atomic‐resolution non‐contact AFM imaging reveal rectangular flakes of nanographene featuring parallel pairs of zig‐zag and armchair edges resulting from the lateral fusion of two pentacene subunits. The synthesis of a novel molecular precursor 6, 6′‐bipentacene, itself a synthetic target of interest for optical and electronic applications, is also reported. The scalable synthetic strategy promises to afford access to a structurally diverse class of extended periacenes and related polycyclic aromatic hydrocarbons as advanced materials for electronic, spintronic, optical, and magnetic devices. Abstract : Zip it up : Synthesis and atomic‐resolution non‐contact AFM imaging of a surface‐stabilized peripentacene is reported. The key intermediate is the metastable 6, 6‐bipentacene precursor, which was obtained through a Staudinger‐type diazo‐thioketone coupling followed by selective 1, 4‐elimination.